Electronic Training Technology on Mathematics of Students Oriented to Work in Nuclear Industry - Vasilenko, N. P.; Chabanova, N. I. (Глобальная ядерная безопасность, 2022)
The article presents the developed and tested technology of e-learning for students at the university. It gives practical examples on the organization of the educational process in accordance with this technology in the mathematical preparation of students. The significance of this approach for the mathematical preparation of students oriented to work in the nuclear industry in connection with the digitalization of all processes in the industry is shown. The effectiveness of the use of this technology in the educational process is confirmed by studies on the level of preparation of students in mathematics, their satisfaction with the organization of the educational process and the dynamics of the students' mathematical intelligence.